Properties Of a Carbamide Composition with A Metal Complex Hardener and Activated Fillers - Juraeva F.D.; Mazhidov S.R. (Zien Journals, 2021)
The article presents analytical materials on the results of studies of chemical patterns and mechanisms of polycondensation reactions occurring in nanostructures of urea composition, the formation of polymer structures, as well as the properties of composite systems by methods of physico-chemical analysis of urea-formaldehyde composition with metal-complex hardener and activated filler.
Keywords: Urea formaldehyde; polymer; activated fillers; heat resistance; composition